Why is Communicating the Circular Bioeconomy so Challenging? - Alexandru Giurca (Circular Economy and Sustainability, 2022)
The circular bioeconomy concept has been around for years now, yet despite increased efforts to popularize it, the concept has so far gained little public attention. Communicating this concept effectively, therefore, poses an important challenge. This commentary synthesizes what is known, presumed, and still unknown about how to effectively communicate about the circular bioeconomy. It postulates that the circular bioeconomy communication challenge appears due to three main reasons: (i) one rooted in differing conceptualizations and competing discourses; (ii) one rooted in normativity; and (iii) due to several knowledge gaps in the communication process. These postulations are backed by examples from the growing body of social-scientific literature on the topic. Finally, it provides a series of lessons learned and some suggestions for future research on circular bioeconomy communication. The insights provided here are useful for environmental communications, and the society and technology scientific communities, as well as for policymakers, practitioners, and communication experts interested in effectively communicating the circular bioeconomy.
Keywords: 330; Circular bioeconomy; Communication; Discourses; Normativity; Communication process